دراسة تأثير الرسوبيات في سد الثورة - Hammad, Mounzer; Ghanam, Orwa (Latakia University Journal -Engineering Sciences Series, 2019)
دراسة تأثير الرسوبيات في سد الثورة منذر حمّاد عروة غنم تُعاني مُعظم السدود حول العالم من مشكلة الترسيب في بحيراتها، وتولى هذه المشكلة حالياً الكثير من الاهتمام لتأثيرها على استطاعة تخزين البحيرة وتحديد العمر التشغيلي للسد بالإضافة إلى دورها في التحديد المناسب لمواقع مآخذ الري والمفرغات السفلية والمنشآت الموجودة على السد أو في البحيرة. إنَّ الهدف من هذا البحث هو دراسة تأثير الرسوبيات على تخزين بحيرة سد الثورة والتنبؤ بتوزع الرواسب فيها بطريقة تزايد المساحة وتحديد حجم التخزين الميت، ودراسة كفاءة حجز الرواسب في بحيرة السد وتحديد عمر السد من أجل سيناريوهات مختلفة. بيَّنت نتائج الدراسة التأثير الواضح والمهم للرسوبيات على منحنيات مساحة التخزين وحجم التخزين بالعلاقة مع عمر السد، حيث أنّه كلما ازداد عمر السد ازداد حجم الرسوبيات في البحيرة الأمر الذي يؤدي إلى تقليل مساحة وحجم التخزين في البحيرة، كما بيت السيناريوهات المقترحة لدراسة كفاءة الحجز أنه كلما ازداد مقدار تخفيض استطاعة التخزين التصميمية، كلما ازدادت كفاءة حجز الرسوبيات ونقص حجم التخزين المفيد، وبالتالي نقص عمر السد. Most of the dams around the world suffer from the problem of sedimentation in their reservoirs, and this problem is currently given much attention due to its important effect on storage capacity of the reservoirs and determining the operational life of the dam, as well as its role in proper identification of the locations of water intakes, bottom outlets and installations on the dam or in the reservoir. The objective of this work is to study the effect of sediments on the storage capacity of Al-Thawra dam and to predict the distribution of sediments in the reservoir of the dam using area increment method, to determine dead storage volume, to study the trap efficiency of the sediments in the reservoir of the dam and to determine the life of the dam for different scenarios. The results of the study revealed the clear and important effect of the sediments on area-storage capacity curves (ASC) in relation to the life of the dam. The larger is the age of the dam, the larger is the sediments volume in the reservoir with the consequent reduction of the reservoir storage volume and area. Proposed scenarios to study trap efficiency showed that the greater the reduction in design storage capacity, the greater the trap efficiency of sediments and the reduction of useful storage volume, thus reducing the life of the dam.